Intergranular crack tip oxidation in a Ni-base superalloy - Viskari, L; Hörnqvist, M; Stiller, K; Moore, K; Cao, Y (2013)
High-temperature intergranular crack tip oxidation under a single 600 s long sustained tensile load at 700 °C was studied for the Ni-base superalloy Allvac 718Plus. High-resolution analytical techniques showed oxidation to take place at and immediately ahead of the tip of an open crack, forming a closed but layered oxide structure about the prior (now oxidized) grain boundary. Near the prior grain boundary the oxide is Ni-rich, with a Co-enriched layer furthest away from the metal and a Fe-enriched region below this. A Cr-rich oxide is present below the outer Ni-rich oxides throughout the crack, also in the direction of crack growth. This is believed to have a hindering effect on oxidation ahead of the crack. Ni(Nb,Al) γ′ precipitates close to the grain boundaries were found to oxidize and form regions of near-stoichiometric NiO within the oxide layers. Remaining constituents of γ′ (e.g. Al and Nb) were found to be enriched in the surrounding oxidized matrix and also to produce thin oxide layers near the interface between the unoxidized metal and the Cr-rich oxide. The formation of the crack tip oxides is discussed with regard to thermodynamics, kinetics and the influence of applied mechanical load. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.